2003
DOI: 10.1381/096089203764467261
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis of Gluteal Muscles Leading to Renal Failure: A Potentially Fatal Complication of Surgery in the Morbidly Obese

Abstract: This is an important and potentially fatal complication of bariatric surgery. Very obese male patients with prolonged surgery are at risk of gluteal muscle necrosis with consequent renal failure, which we hypothesize is due to pressure by the operating-table leading to rhabdomyolysis and the creation of a compartment syndrome. Prevention may be aided by attention to intraoperative padding and positioning, and by limiting the duration of the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 6 publications
3
59
0
11
Order By: Relevance
“…The author emphasizes that a higher incidence could have been found if CK dosage were a routine for these patients. Bostanjian et al 11 have reported six cases of rhabdomyolysis in 650 morbidly obese patients submitted to laparoscopic gastric bypass (0.9% incidence). All six cases started with gluteus bed wounds reaching mean CK levels of 26 000 U/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The author emphasizes that a higher incidence could have been found if CK dosage were a routine for these patients. Bostanjian et al 11 have reported six cases of rhabdomyolysis in 650 morbidly obese patients submitted to laparoscopic gastric bypass (0.9% incidence). All six cases started with gluteus bed wounds reaching mean CK levels of 26 000 U/L.…”
Section: Discussionmentioning
confidence: 99%
“…Ela pode ocorrer com maior freqüência do que se imagina 4 , pois a anestesia propicia algumas condições de risco como a imobilização prolongada, a longa duração de certos procedimentos cirúrgicos e posições cirúrgicas anatomicamente forçadas 3,5-10 . Além disso, a obesidade tem sido apontada como fator de risco 3,11,12 . Há pouca referência a esse tipo de complicação, em revistas de anestesia 5 , tornando rara a discussão sobre o assunto.…”
unclassified
“…It appears to be the result of pressure necrosis of the muscles, initially by unrelieved pressure on the operating table, and amplified by edema and swelling within the gluteal muscle compartment [19]. If unrecognized, extensive skin necrosis overlying the gluteal muscles may develop (Figure 3).…”
Section: Rhabdomyolysismentioning
confidence: 99%
“…Bostanjiyan serisinde GKS gelişen altı hastanın üçü ölmüştür (8). Yine bizim olgumuzda ölümle sonuçlandı.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
“…Bu nedenle korumacı yaklaşımlar oldukça önemlidir. Bu yaklaşımlar arasında operasyon boyunca basınç noktalarına ilave pad konulması, özel matress ya da havalı yatak seçimi, çift operasyon masası kullanımı, operasyon sırasında iki saatte bir pozisyon değişimi, süper-süper obezlerde operasyon süresinin daha kısa olduğu sleeve gastrektomi gibi yöntemlerin seçilmesi sayılabilir (2,8,9). Rabdomyoliz yaptığı bilinen statinler gibi ilaçların kesilmesi konusu tartışmalıdır (10).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified